Influencia en las redes sociales en los emprendimientos del mercado Municipal del cantón Buena Fe, año 2022 - Peñaloza Zambrano, Gabriel Leomaiz (2022)
This case study analyzes the incidence of social networks as advertising media for the ventures of the municipal market of the canton of Buena Fe, with the objective of determining the incidence of social networks in the merchants of the municipal market of Buena Fe. To search for information successfully, this work mixes qualitative and quantitative research, with a descriptive methodology using the survey technique with its respective instrument, the questionnaire to entrepreneurs to obtain information on how they approach social networks when they promote their products or services. To understand the advertising field, a cautious investigation and critical analysis was carried out on the subject. With the completion of the project, it can be deduced that social networks, in addition to being means of communication, are also viable channels for business advertising. It is worth mentioning that it was concluded that social networks are the advertising medium with the most customer acquisitions worldwide given the boom left by the pandemic, resulting in the new digital society.